Validation of TROPOMI Surface UV Radiation Product ... : التحقق من صحة منتج الأشعة فوق البنفسجية السطحية TROPOMI ... - Kaisa Lakkala; Jukka Kujanpää; Colette Brogniez; Nicolas Henriot; Antti Arola; Margit Aun; Frédérique Auriol; A. F. Bais; Germar Bernhard; Veerle De Bock; Maxime Catalfamo; Christine Deroo; et al. (OpenAlex, 2020)
Abstract. The TROPOspheric Monitoring Instrument (TROPOMI) onboard the Sentinel-5 Precursor (S5P) satellite was launched on 13 October 2017 to provide the atmospheric composition for atmosphere and climate research. The S5P is a sun-synchronous polar-orbiting satellite providing global daily coverage. The TROPOMI swath is 2600 km wide, and the ground resolution for most data products is 7.2 x 3.5 km2 (5.6 x 3.5 km2 since 6 August 2019) at nadir. The Finnish Meteorological Institute (FMI) is responsible for the development and processing of the TROPOMI Surface Ultraviolet (UV) Radiation Product which includes 36 UV parameters in total. Ground-based data from 25 sites located in arctic, subarctic, temperate, equatorial and antarctic areas were used for validation of TROPOMI overpass irradiance at 305, 310, 324 and 380 nm, overpass erythemally weighted dose rate/UV index and erythemally weighted daily dose for the period from 1 January 2018 to 31 August 2019. The validation results showed that for most sites ... : الخلاصة: تم إطلاق جهاز TROPOspheric Monitoring Instrument (TROPOMI) على متن القمر الصناعي Sentinel -5 Precursor (S5P) في 13 أكتوبر 2017 لتوفير التكوين الجوي لأبحاث الغلاف الجوي والمناخ. S5P هو قمر صناعي متزامن مع الشمس في المدار القطبي يوفر تغطية يومية عالمية. يبلغ عرض رقعة TROPOMI 2600 كم، ودقة الأرض لمعظم منتجات البيانات هي 7.2 × 3.5 كم 2 (5.6 × 3.5 كم 2 منذ 6 أغسطس 2019) في الحضيض. المعهد الفنلندي للأرصاد الجوية (FMI) مسؤول عن تطوير ومعالجة منتج الأشعة فوق البنفسجية السطحية TROPOMI الذي يتضمن 36 معلمة للأشعة فوق البنفسجية في المجموع. تم استخدام البيانات الأرضية من 25 موقعًا تقع في المناطق القطبية الشمالية وشبه القطبية والمعتدلة والاستوائية والقارة القطبية الجنوبية للتحقق من إشعاع الجسر TROPOMI عند 305 و 310 و 324 و 380 نانومتر، ومعدل الجرعة المرجحة بالحمراء/مؤشر الأشعة فوق البنفسجية والجرعة اليومية المرجحة بالحمراء للفترة من 1 يناير 2018 إلى 31 أغسطس 2019. أظهرت نتائج التحقق من الصحة أنه بالنسبة لمعظم المواقع، كانت 60–80 ٪ من بيانات TROPOMI في حدود ±20 ٪ من البيانات الأرضية لظروف السطح الخالية من الثلوج. ...